Group work with sexually abused children : a practitioner's guide - Grotsky, Lynn (Interpersonal violence., 2000)
Following an overview of the theory and literature of group therapy with children, this manual provides 60 complete group exercises to build psycho-social skills, including trust building, self esteem and healing the inner child.